Remediasi Miskonsepsi Konsep Hukum Newton dengan Menggunakan Metode Eksperimen di Kelas X SMA Negeri 3 Langsa - Hotmauli Sinaga; Muhammad Yakob; Rizky Nafaida (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
Studying physics at school tends to be directed at the ability to memorize legal sounds and remember only formulas. While the process of learning through direct experience and discovery is often overlooked, so students do not understand the concept of physics/ misconceptions occur and are not able to apply in real life. By using experimental method can reduce misconceptions in students who directly involve in practicum. The purpose of this study was to look at the effect of the experimental method on reducing the misconceptions of students of class ten science two of Senior High School 3 Langsa. The method used in this research methods. The population in this study were 204 students of class ten natural sciences consisting of 6 classes. While the sample is as many as 70 students from two classes, namely class ten natural 2 as an experimental class totaling 32 students and class ten natural 1 as a control class of 33 students. Based on the results of the study showed t count = 8,70 with t table = 1,145. The magnitude of the effect of the experimental method to reduce students misconception on Newton’s Law concept in class ten natural 2 of Senior High School Negeri 3 Langsa on average by 44%. So it can be concluded that there influence of the experimental method to reduce misconceptions on the Newton Law concept in class ten Senior High School Negeri 3 Langsa. Keywords : Newton’s Law Concept, Experimental Method, Misconception